Palmitoylated cellulose nanocrystal/polycarbonate composite with high mechanical performance and good transparency. Issue 2 (5th November 2022) - Xie, Zhongyuan; Wang, Xingjuan; Chen, Zhangyun; Jiang, Hua
Abstract: To fabricate polycarbonate (PC) composites with high mechanical and optical properties, PC composite films reinforced by cellulose nanocrystals esterified using palmitoyl chloride (palmitoylated cellulose nanocrystal [PAL‐CNCs]) were fabricated by casting‐evaporation and characterized by several techniques. It was shown that the PAL‐CNCs with a substitution degree of 0.43 and the crystalline index of 53.3% were better dispersed in chloroform and tetrahydrofuran, and achieved a water contact angle of 81.0°. The crystallite size and crystalline index of the PC in the composite film significantly increased to more than 5.2 nm and 51.5%, respectively, after the incorporation of the PAL‐CNCs. The PC composite film had an increase of 91.4% in tensile strength, 84.1% in Young's modulus, and a decrease of 5% in impact strength. Meanwhile, its UV–Vis‐light transmittance was above 90%. Therefore, the palmitoylated ‐CNCs were a better candidate for engineering PC composites with high mechanical performance and transparency. Abstract : Palmitoylated cellulose nanocrystals (CNCs)/polycarbonate (PC) nanocomposite films were prepared by casting/evaporation. The results showed that palmitoylated‐CNCs increased the crystalline domains of the PC and dramatically improved the mechanical strength of the composite film while maintaining its high transparency.